Inheritance of Root Characters and Their Relations to Drought Resistance in Rice - Ekanayake, I.J.; O'Toole, J.C.; Garrity, D.P.; Masajo, T.M. (Wiley, 1985)
The ability of rice plants to tolerate drought stresses is associated with root system characters. However, the genetics of root traits are not well understood. Hence, the inheritance of six root characters of rice (Oryza sativa L.) was studied using the parents, F1, F2, and F3 populations of the cross IR20✕MGL‐2. Plants were grown in a hydroponic culture solution in a phytotron glasshouse and in an upland drought screening nursery. A polygenic system of inheritance was indicated for the root characters. The F1 plants had root systems characterized by thick, deep roots with a higher lateral and vertical distribution than the low parent (IR20), and the heterosis was significant and positive. The additive and dominant genetic effects contributed equally to the expression of all root traits. Both progeny parent regression of F3 and F2, and the narrow sense heritability estimates in F3 were high for root thickness (0.61 and 0.80), root dry weight (0.56 and 0.92) and root length density (0.44 0.77). Selection of root types, based on individual plant performance, should be successful in early segregating generations if selection is practiced on these characters. Associations between root characters and plant height, tiller number, and shoot weight were positive and significant. Five root characters were significantly correlated with the visual field drought resistance scores and with leaf water potential, confirming the role of root characters in maintaining high leaf water potential under water stress.